Aplikasi Citizen Journalism di Era Konvergensi Media - Rahmat Edi Irawan (Humaniora, 2014)
Citizen journalism has now become one of the most developed television program concepts. If the concept was initially more widely used in radio and online media, this time with easier and cheaper technology coverage and delivery of images, it is a concept that provides a place for people to become amateur journalist that can also be easily applied in the medium of television. Research raised the issue on how the concept and implementation of citizen journalism on television in the era of media convergence. The purpose of this study is to explain concepts and demonstrate the implementation of citizen journalism on television in the era of media convergence. Research used qualitative method in which data were obtained using literature study. Results of the study showed that the implementation of citizen journalism on television is also increasingly facilitated by the entry of the television in the era of media convergence, or different media mingle, such as television with printed, radio, and Internet media. The era of media convergence makes the concept of citizen journalism can be more developed, because the platform or media distribution is also increasingly varied for amateur journalist. However, the system equipment that must be provided, human resources that must be owned, as well as huge capital to be owned make a few television stations open a lot of platforms to provide space for amateur journalist in citizen journalism.